1997
DOI: 10.1038/bjc.1997.57
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of DMBA-induced mammary carcinogenesis in rats by low-dose EPA and DHA

Abstract: Summary We investigated the effects of low-dose eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) on the incidence and growth of 7,12-dimethylbenz(a)anthracene (DMBA)-induced mammary carcinoma in rats fed a high-fat (HF) diet. We also examined the effects of these treatments on the fatty acid composition of tumour and serum. Tumour incidence was significantly decreased by the administration of low-dose EPA and DHA, whereas their inhibitory effects on tumour growth did not reach significance. Serum ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
44
0
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 29 publications
4
44
0
3
Order By: Relevance
“…Tamoxifen reduced cancer incidence, cancer multiplicity, and cancer burden in the absence of any effect of the n-3:n-6 ratio (Table 3). This finding, although consistent with the mammary gland density data (Table 2) and the null findings reported in references 12, 36, and 38, disagrees with other published reports in which high levels of dietary fish oil were reported to protect against chemically induced mammary carcinogenesis (10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Tamoxifen reduced cancer incidence, cancer multiplicity, and cancer burden in the absence of any effect of the n-3:n-6 ratio (Table 3). This finding, although consistent with the mammary gland density data (Table 2) and the null findings reported in references 12, 36, and 38, disagrees with other published reports in which high levels of dietary fish oil were reported to protect against chemically induced mammary carcinogenesis (10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, the preclinical data on the role of n-3 fatty acids in mammary carcinogenesis is similarly mixed (inhibition, no effect, or promotion of carcinogenesis), and the quality of the experiments varies so markedly that it is difficult to compare results across studies (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). These circumstances prompted the work reported herein.…”
Section: Introductionmentioning
confidence: 99%
“…It has been postulated that the risk of breast cancer can be influenced by certain dietary components such as the amount and type of dietary fats ingested (3)(4)(5)(6)(7). Among the fatty acids, omega-3 (n-3) and omega-6 (n-6) fatty acids have been suggested to decrease and increase breast cancer risk, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Both epidemiologic and experimental studies have suggested that n-3 PUFAs can exert a chemopreventive effect against some common tumours and multiple mechanisms have been involved in this activity, including suppression of neoplastic transformation (Noguchi et al, 1997), cell cycle arrest (Albino et al, 2000), induction of apoptosis (Latham et al, 1999), antiangiogenesis and suppression of metastasis Senzaki et al, 1998). This study was designed to assess the possible interaction of n-3 PUFAs and ionising radiation, which has not been reported before.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mechanisms are involved in this chemopreventive activity, including suppression of neoplastic transformation (Noguchi et al, 1997), cell cycle arrest (Albino et al, 2000), induction of apoptosis (Latham et al, 1999), antiangiogenesis and suppression of metastasis (Suzuki et al, 1997;Senzaki et al, 1998). However, a common feature of most biological effects is the inhibition of eicosanoid production from n-6 fatty acid precursors.…”
mentioning
confidence: 99%